ANALISIS DISTRIBUSI NANOPARTIKEL Fe3O4 TERHADAP PENYERAPAN LOGAM BERAT Pb - Sartika, Dewi; Malis, Eko; Mangunang, Emmistasega Subama (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2019)
Magnetic nanomaterial Fe3O4 has pabricated using coprecipitation methods for 90 minutes with temperatur 60oC . Pabrication product of this sample were coloured black powder. Characterisation of Fe3O4 used Transmission Electron Microscopy (TEM). Characterization result studied were density using J-image software. Mixing Fe3O4 powder into liquid waste has goal to determine the level of absorption of Fe3O4 magnetic nanomaterials to heavy metals contained in waste. Particle density has a big potential to absorb heavy metals, especially Pb. At the density level of the densest Fe3O4 particles shows the optimal absorption ability of Pb metal absorbed at a concentration of 0,56 grams with an absorption percentage of 99,99%.